Microbial-based natural products as potential inhibitors targeting DNA gyrase B of Mycobacterium tuberculosis: an in silico study - Elsaman, Tilal; Mohamed, Magdi Awadalla; Mohamed, Malik Suliman; Eltayib, Eyman Mohamed; Abdalla, Abualgasim Elgaili (Frontiers in Chemistry, 2025)
IntroductionSince the emergence of Mycobacterium tuberculosis (MBT) strains resistant to most currently used anti-tubercular drugs, there has been an urgent need to develop efficient drugs capable of modulating new therapeutic targets. Mycobacterial DNA gyrase is an enzyme that plays a crucial role in the replication and transcription of DNA in MBT. Consequently, targeting this enzyme is of particular interest in developing new drugs for the treatment of drug-resistant tuberculosis, including multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB).MethodsIn the present study, multiple computational tools were adopted to screen a microbial-based natural products database (NPAtlas) for potential inhibitors of the ATPase activity of MBT DNA gyrase.Results and discussionTwelve hits were initially identified as the top candidates based on their docking scores (ranging from −9.491 to −10.77 kcal/mol) and binding free energies (−60.37 to −73.21 kcal/mol). Following this, computational filters, including ADME-T profiling and pharmacophore modeling, were applied to further refine the selection. As a result, three compounds 1-Hydroxy-D-788-7, Erythrin, and Pyrindolol K2 emerged as the most promising, exhibiting favorable drug-like properties. Notably, 1-Hydroxy-D-788-7, an anthracycline derivative, demonstrated superior binding affinity in molecular dynamics simulations. The RMSD values, ranging from 1.7 to 2.5 Å, alongside RMSF analysis and a detailed evaluation of the established interaction forces, revealed that 1-Hydroxy-D-788-7 was the strongest binder to Mycobacterial DNA Gyrase B. The stable binding and favorable interaction profile highlighted 1-Hydroxy-D-788-7 as a top hit. These comprehensive computational findings strongly support the potential of 1-Hydroxy-D-788-7 as an effective anti-TB lead compound, warranting further experimental validation to confirm its therapeutic efficacy.